Artocarpin, A Promising Compound as Whitening Agent and Anti-skin Cancer - Enos T Arung; Sipon Muladi; Edi Sukaton; Kuniyoshi Shimizu; Ryuichiro Kondo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
In our search for natural products from wood on cosmetics and drugs purposes and on the basis of melanin biosynthesis assay guided fractionation, artocarpin was isolated from wood of Nangka (Artocarpus heterophyllus). To evaluate the potency as a whitening agent of artocarpin and its anti-skin cancer (cytotoxicity effect), the MTT assay was used to evaluate its cytotoxicity on cells and melanin biosynthesis assays was performed to determine its whitening agents potency. The evaluation of cytotoxicity on B16 melanoma cells of Artocarpin resulted the IC50 was 10.3 µM and melanin biosynthesis assay with IC50 6.7 µM with out cytotoxicity. Based on the results, suggested that artocarpin have a potent to be developed as whitening agent and skin cancer drug.